2021
DOI: 10.1021/acs.jctc.1c00919
|View full text |Cite
|
Sign up to set email alerts
|

Extended Benchmark Set of Main-Group Nuclear Shielding Constants and NMR Chemical Shifts and Its Use to Evaluate Modern DFT Methods

Abstract: An extended theoretical benchmark set, NS372, for light main-group nuclear shieldings and NMR shifts has been constructed based on high-level GIAO-CCSD­(T)/pcSseg-3//CCSD­(T)/cc-pVQZ reference data. After removal of the large static-correlation cases O3, F3 –, and BH from the statistical evaluations for the 17O, 19F, and 11B subsets, the benchmark comprises overall 372 shielding values in 117 molecules with a wide range of electronic-structure situations, containing 124 1H, 14 11B, 93 13C, 43 15N, 31 17O, 47 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
150
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(157 citation statements)
references
References 133 publications
5
150
2
Order By: Relevance
“…147 It is also known to provide excellent predictions of NMR shifts in closed-shell systems of main group elements. 101,[148][149][150][151][152] However, as shown in Table 2, for the case of cyanomethyl radicals the DSD-PBEP86 functional suffered from instabilities that resulted in erratic spin density on the nitrogen atom. Special care has to be taken when applying double hybrid functionals to open-shell systems.…”
Section: Prediction Of Hyperfine Coupling: the Challengementioning
confidence: 99%
“…147 It is also known to provide excellent predictions of NMR shifts in closed-shell systems of main group elements. 101,[148][149][150][151][152] However, as shown in Table 2, for the case of cyanomethyl radicals the DSD-PBEP86 functional suffered from instabilities that resulted in erratic spin density on the nitrogen atom. Special care has to be taken when applying double hybrid functionals to open-shell systems.…”
Section: Prediction Of Hyperfine Coupling: the Challengementioning
confidence: 99%
“…Recent work has demonstrated that a more rigorous treatment is provided by the Dobson ansatz for τ, 42 44 although the differences for some functionals, such as TPSS, are small. 21 We have included data calculated with TPSS and the Dobson ansatz in the Supporting Information ( Table S9 ), and indeed, the results are very similar.…”
Section: Structures and Methodsmentioning
confidence: 73%
“…However, in the presence of heavier nuclei, this might lead to deviations—in the case of sulfur, up to 0.5 ppm for 1 H SCs. 21 , 46 , 47 …”
Section: Structures and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The functional has been supplemented by D4 dispersion corrections . LH20t-D4 has been demonstrated to be one of the best-performing rung 4 functionals for general main-group energetics (GMTKN55 test set), for transition-metal thermochemistry and barriers, and for many spectroscopic parameters. However, it has not been constructed to give low FSEs or to generally account for sc effects.…”
Section: Theorymentioning
confidence: 99%